Effect of Vocational Rehabilitation Training Camp on Patients with Spinal Cord Injury Returning to Society - Lingjuan RAO; Li DAI; Li CHEN; Xiaoling LI; Jichao XIONG; Qingjun YANG; Huazhong YANG; Jinlong CUI (康复学报)
Objectives:To investigate the therapeutic effect of vocational rehabilitation training camp on patients with spinal cord injury (SCI) returning to society.Methods:A total of 34 patients with spinal cord injury who were hospitalized and received rehabilitation treatments in Xiangya Boai Rehabilitation Hospital from October 2017 to October 2019 were recruited and randomly divided into control group (16 cases) and observation group (18 cases) according to the random number table method. The control group received conventional rehabilitation treatment (including basic training, daily life activity training, traditional Chinese medicine therapy, etc.) for 6 hours a day, 5 days a week, for 12 weeks. The observation group added 2 weeks of vocational rehabilitation training camp on the basis of conventional rehabilitation treatment, 10 hours a day, 5 days a week, for 2 consecutive weeks, a total of 14 weeks. Patients in two groups were evaluated using general self-efficacy scale (GSES), community integration questionnaire (CIQ), and the lam assessment of stages of employment readiness (LASER) before and after treatment. The statuses of returning to work of patients were followed up by telephone six months after discharge.Results:There were no statistically significant differences between the two groups in GSES scores and CIQ scores before treatment (P> 0.05). There were statistically significant differences in GSES scores (20.89±4.86∶31.44±3.42), CIQ-family integration scores (4.39±1.24∶10.50±1.72), CIQ-social integration scores (2.78±0.94∶8.06±1.86), CIQ-production activity scores (0.50±0.62∶3.06±0.80) and LASER scores of the observation group before and after treatment (P< 0.05). There were statistically significant differences in GSES scores (22.06±5.53∶28.63±4.54), CIQ-family integration scores (4.69±1.14∶6.69±1.49), CIQ-social integration scores (3.75±0.93∶6.19±1.17), CIQ-production activity scores (0.75±0.68∶2.13±0.62) and LASER scores of the control group before and after treatment (P< 0.05). After treatment, there were statistically significant differences in GSES scores (31.44±3.42∶28.63±4.54), CIQ-family integration scores (10.50±1.72∶6.69±1.49), CIQ-social integration scores (8.06±1.86∶6.19±1.17), CIQ-production activity scores (3.06±0.80∶2.13±0.62), and LASER scores between the two groups (P< 0.05). Six months after discharge, the rate of returning to work of SCI patients in the observation group was significantly higher than that of the control group (P< 0.05).Conclusion:Vocational rehabilitation training camp can significantly improve the general self-efficacy, community integration, willingness to work and the rate of returning to work of patients with spinal cord injury.